An Experimental Animal Study: Electroacupuncture Facilitates Antiviral Immunity Against Hepatitis B Virus Through the IFN-γ/JAK/STAT Axis - Yang Y; Ge F; Luo C; Liao C; Deng J; Yang Y; Chen Y; Guo X; Bai Z; Xiao X; Tang C (Dove Medical Press, 2024)
Yan Yang,1,* Feilin Ge,2,* Chen Luo,1 Cai Liao,1 Junyuan Deng,1 Yunhao Yang,1 Yang Chen,1 Xiao Guo,1 Zhaofang Bai,3 Xiaohe Xiao,3 Chenglin Tang1 1College of Traditional Chinese Medicine, Chongqing Medical University, Chongqing, 400010, People's Republic of China; 2Department of Chinese Medicine, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450052, People's Republic of China; 3Senior Department of Hepatology, the Fifth Medical Center of Chinese PLA General Hospital, Beijing, 100039, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaohe Xiao, Senior Department of Hepatology, The Fifth Medical Center of Chinese PLA General Hospital, Beijing, People's Republic of China, Email pharmacy302xxh@126.com Chenglin Tang, College of Traditional Chinese Medicine, Chongqing Medical University, Chongqing, People's Republic of China, Email tangchenglin@cqmu.edu.cnBackground: Chronic hepatitis B (CHB) remains a global health challenge, necessitating innovative therapeutic strategies. Enhancing the body's immune response against the hepatitis B virus (HBV) emerges as a fundamental strategy for achieving a functional cure. While acupuncture has shown potential in immune modulation, its specific anti-HBV effects are not well understood. This study evaluates the potential of electroacupuncture (EA) in HBV infection and explores its underlying immunological mechanisms using a mouse model.Methods: HBV-infected mice were established using the high-pressure hydrodynamic method and divided into four groups: normal saline (NS), EA, sham EA (SE), and tenofovir disoproxil fumarate (TF), with n = 6 per group. During treatment, blood was collected every Sunday via the orbital sinus to monitor HBV DNA, HBsAg, and HBeAg levels. Transcriptomics and metabolomics analyses were employed to unearth clues regarding EA's anti-HBV mechanism. Validation of these mechanisms included splenic T-cell flow analysis, Western blotting, RT-qPCR, immunofluorescence, and ELISA.Results: Serum HBV DNA levels decreased by 1.10, 0.19, and 1.98 log10 IU/mL in the EA, SE, and TF-treated mice, respectively, compared to the NS. Concurrently, the hepatic HBV DNA levels decreased by 1.09, 0.24, and 2.03 log10 IU/mL. EA also demonstrated superior inhibition of HBV antigens, with serum HBeAg levels decreasing by 43.86%, 8.74%, and 8.03%, and serum HBsAg levels decreasing by 28.01%, 0.26%, and 9.39% in the EA, SE, and TF groups, respectively. Further analysis through transcriptomics and metabolomics revealed that EA's anti-HBV effects primarily hinge on immune modulation, particularly the IFN-γ/JAK/STAT pathway and taurine metabolism. EA also increased the ratio of splenic CD8+ CD69+ and CD8+ IFN-γ+ T-cells while upregulating key proteins in the JAK/STAT pathway and cytokines associated with antiviral immunity.Conclusion: EA manifests inhibitory effects on HBV, particularly in antigen suppression, with its mode of action intricately linked to the regulation of IFN-γ/JAK/STAT.Keywords: hepatitis B virus, electroacupuncture, antiviral activity, immune modulation, IFN-&#x03B3